Mechanical model analysis and reliability design approach of Quartz Flexible Accelerometer under fractured state - Tingyu Xiao; Chunxi Zhang; Lailiang Song; Longjun Ran; Wanying Huang (IET Circuits, Devices and Systems)
Abstract Currently, the Quartz Flexible Accelerometer (QFA) mounted for the applications working in high acceleration environment are suffering from the fracture of the flexible beams under external acceleration shock. This paper presents the mechanical model and reliability design approach of QFA to maintain the measuring ability under a fractured state. The structural parameters changed significantly in the mechanical model under a fractured state compared to those in the original model. A modified structure to maintain the measuring ability of QFA under a fractured state is designed with the reference of the sensitive module in Electrostatic Suspended Accelerometer (ESA). The corresponding close‐loop system is corrected and discretised to ensure the stability requirements of the mechanical model. A static experiment is conducted to prove the effectiveness of the proposed model by a prototype QFA with completely fractured flexible beams. The result shows helpful on the preliminary research for QFA with the similar sensitive structure to ESA.